Praxishandbuch Bibliotheksbau : Planung - Gestaltung - Betrieb - Hauke, Petra 1946- HerausgeberIn; Werner, Klaus Ulrich 1956- HerausgeberIn (Reference, 2016)
The 'Practical Handbook of Library Construction' deals with all aspects of building and equipping a library. It covers planning, site selection, exterior facilities, space allotment, tendering, financing, laws and standards, library facilities, technical infrastructure, transport systems, classroom spaces, and barrier-free design. The handbook includes an extensive bibliography